Difficult to Treat Focal, Stiff Person Syndrome of the Left Upper Extremity. (25th October 2017) - Esplin, Nathan E.; Stelzer, John W.; Legare, Timothy B.; Ali, Sayed K.
Abstract : Background . Stiff person syndrome (SPS) is a rare neurologic disorder characterized by muscle rigidity. It is a disorder of reduced GABA activity leading to increased muscle tone and often painful spasms. It generally presents in the axial musculature but rarely can involve only one limb, typically a lower extremity. In rare cases it can be paraneoplastic which generally resolves on treatment of the underlying neoplasm. Case Report . A 46-year-old male with a history of Hodgkin's Lymphoma in remission presented with left upper extremity pain secondary to a diagnosis of Stiff Person Syndrome limited to his left upper extremity. He had previously benefitted from plasmapheresis and was on diazepam and baclofen at home with relatively good control of his symptoms. SPS had previously been diagnosed with EMG and anti-GAD-65 antibody titers and was confirmed by an elevated anti-GAD-65 antibody titer. He was treated with plasmapheresis and maximum doses of medical treatment including botulinum toxin with only transient mild improvement in his symptoms. Conclusion . This case represents a case of a rare disease that was refractory to all known therapies. It outlines the need for further understanding of this disorder in order to provide better symptomatic treatment or potentially more definitive care.